17 NO'LU ANTAKYA ŞER'İYYE SİCİLİ - KARADAĞ, SERMİL GÜNGÖR (Fırat Üniveristesi, 2003)
Tezimin birinci bölümünde Osmanlı Devleti'nde Adalet Teşkilâtı ve Şerciyye Sicilleri hakkında bilgi verdim. Ayrıca bu bölümde Osmanlı Devleti'nde Kadılık Kurumu, Mahkeme ve Mahkeme Görevlileri ve Şerciyye Sicillerinin muhtevalarını inceledim. Tezimin ikinci bölümünde 17 Numaralı Antakya Şerciyye Sicili'nde yer alan belgelerin konularına göre tasnifim yaptım. Sonra sonuç, bibliyografya ve ekleri koyarak tezimi tamamladım. Anahtar Kelimeler:Kadı,Sicil,Mahkeme,Belge

In the first chapter of my thesis, I gave education about justice constitutions and Şerciyye registers in the Otoman Empire. In addition inthis chapter I investigated kadılık society,court and the employers of court,cadi and the cadi and the cadi's duties and Şerciyye's registers contents in the Otoman Empire. In the second chapter of my thesis Imade the arranging of the documents which are existingin the numbered 17 of Antakya Şerciyye register. Then I made the summarize of documents, text's transciription.In the endjfinished my thesis with putting,bibliography and joints. Key words:Cadi,register, court,document.
Numbered 17 of Antakya Şer'iyye Register
Keywords: Tarih; History